Baseline higher peritoneal transport had been associated with worse nutritional status of incident continuous ambulatory peritoneal dialysis patients in Southern China: a 1-year prospective study. Issue 3 (16th July 2015) - Liu, Yun; Huang, Rong; Guo, Qunying; Yang, Qiongqiong; Yi, Chunyan; Lin, Jianxiong; Yu, Xueqing; Yang, Xiao
Abstract : The aim of the present study was to investigate the relationship between baseline peritoneal transport types and nutritional status in Chinese continuous ambulatory peritoneal dialysis (CAPD) patients. In the present single-centre, prospective study, incident CAPD patients were included from 15 April 2010 to 31 December 2011 and were followed up for 12 months. According to the results of baseline peritoneal equilibration test, patients were divided into lower peritoneal transport group (lower transporters) and higher peritoneal transport group (higher transporters). Nutritional status was evaluated by both subjective global assessment (SGA) and protein–energy wasting (PEW) score. The body composition parameters were assessed by body impedance analysis. A total of 283 CAPD patients were included in the study, of which 171 (60·4 %) were males with a mean age of 47·0 (sd 14·9) years. Compared with lower transporters ( n 92), higher transporters ( n 181) had lower levels of serum albumin (37·1 (sd 4·3) v. 39·6 (sd 4·3) g/l, P < 0·001), serum pre-albumin (356 (sd 99) v. 384 (sd 90) mg/l, P = 0·035), phase angle (6·15 (sd 0·39) v. 6·27 (sd 0·47)°, P < 0·05) and higher rate of malnutrition defined by SGA (52·5 v. 25·0 %, P < 0·001) and PEW score (37·0 v. 14·1 %, P < 0·001) at 1-year of follow-up. Baseline higher peritoneal transport, analysed by multivariate binary logistic regressions, was independently associated with malnutrition (SGA mild to moderate and severe malnutrition: OR 3·43, 95 % CI 1·69, 6·96, P < 0·01; PEW: OR 2·40, 95 % CI 1·08, 5·31, P = 0·03). It was concluded that baseline higher peritoneal transport was independently associated with worse nutritional status of CAPD patients in Southern China.